PP45 'Every day was a learning curve': the experience of implementing COVID-19 triage protocols in UK ambulance services – a qualitative study. Issue 9 (23rd August 2022) - Porter, Alison; Bell, Fiona; Brady, Mike; Brown, Shona; Carson-Stevens, Andy; Duncan, Edward; England, Louise; Evans, Bridie; Foster, Theresa; Gallanders, John; Gunson, Imogen; Harrington, Barbara; et al.
Abstract : Background: TRIM is an evaluation of the models used to triage and manage emergency ambulance service care for patients with suspected Covid-19 during the first wave of the pandemic in 2020. We aimed to understand experiences and concerns of clinical and managerial staff about implementation of triage protocols in call centre and on-scene. Methods: Research paramedics in four study sites across England interviewed purposively selected stakeholders from ambulance services (call handlers, clinical advisors in call centres, clinicians providing emergency response, managers) and ED clinical staff from one hospital per site. Interviews (n=23) were conducted remotely using MS Teams, recorded, and transcribed in full. Analysis generated themes from the implicit and explicit ideas within participants' accounts, following the six stages of analysis described by Braun and Clarke, conducted by a group of researchers and PPI partners working together. Results: We identified the following themes: Constantly changing guidelines – at some points, updates several times a day The ambulance service as part of the wider healthcare system - changes in other parts of the healthcare system left ambulance services as the default option Peaks and troughs of demand - demand fluctuated greatly over time, with workload varying across the ambulance service, including an increased role for clinical advisors A stretched system - resources to respond to patient demand were stretched thinner by staff sickness and isolation, longer job times, and increased handover delays at ED Emotional load of responding to the pandemic - particularly for call centre staff Doing the best they can in the face of uncertainty - in the face of a rapidly evolving situation unlike any which ambulance services had faced before Discussion: Implementing triage protocols in response to the Covid-19 pandemic was a complex and process which had to be actively managed by a range of front line staff, dealing with external pressures and a heavy emotional load.